Animal Models for Assessment of Infection and Inflammation: Contributions to Elucidating the Pathophysiology of Sudden Infant Death Syndrome - Blood-Siegfried, Jane (Frontiers in Immunology, 2015)
Sudden Infant Death Syndrome (SIDS) is still not well understood. It is a diagnosis of exclusion following the sudden and unexpected death of an infant. There are numerous theories about the etiology of SIDS but the exact cause or causes have never been pinpointed. Examination of theoretical pathologies might only be possible in animal models. Development of these models requires consideration of the genetic, developmental and environmental risk factors associated with SIDS, as they need to explain how the risk factors could contribute to the cause of death. These models were initially developed in common laboratory animals to test various hypotheses to explain these infant deaths - guinea pig, piglet, mouse, neonatal rabbit and neonatal rat. Currently there are growing numbers of researchers using genetically altered animals to examine specific areas of interest. This review describes the different systems and models developed to examine the diverse hypotheses for the cause of SIDS and their potential for defining a causal mechanism or mechanisms.